Increase in time spent on social media is associated with modest increase in depression, conduct problems, and episodic heavy drinking. (July 2019) - Brunborg, Geir Scott; Burdzovic Andreas, Jasmina
Abstract: Introduction: Adolescent use of social media has been linked to a range of negative outcomes, but it is still unclear whether the associations are spurious. To address this issue, we examined if within-individual change in time spent on social media was associated with within-individual changes in depression, conduct problems, and episodic heavy drinking in a sample of adolescents using first-differencing models (FD-models). Methods: A sample of 763 Norwegian adolescents (45.1% boys; mean age 15.22 years, standard deviation 1.44) completed two questionnaires 6-months apart. The associations between changes in time spent on social media and symptoms of depression, conduct problems, and frequency of episodic heavy drinking were estimated using FD-models, a statistical technique that effectively controls for all time-invariant individual factors. We also accounted for three time-variant putative confounders: frequency of sports practice, frequency of unsupervised leisure activities, and peer relationship problems. Results: Increases in time spent on social media were associated with increases in symptoms of depression ( b = 0.13 [95% CI: 0.01, 0.24], p = 0.038), increases in conduct problems ( b = 0.07 [95% CI: 0.02, 0.10], p = 0.007), and increases in episodic heavy drinking ( b = 0.10 [95% CI: 0.06, 0.15], p < 0.001), after adjusting for changes in the three hypothesized confounders. The effect-sizes for these relationships were, however, quite modest. Conclusion: Increased time spent on social media was modestly related to increases in depression, conduct problems, as well as frequency of episodic heavy drinking among adolescents.